Graph-powered machine learning / c Alessandro Negro, author. - Negro, Alessandro (Manning Publications, 2021)
In Video Editions the narrator reads the book while the content, figures, code listings, diagrams, and text appear on the screen. Like an audiobook that you can also watch as a video. I learned so much from this unique and comprehensive book. A real gem for anyone who wants to explore graph-powered ML apps. Helen Mary Labao-Barrameda, Okada Manila Upgrade your machine learning models with graph-based algorithms, the perfect structure for complex and interlinked data. In Graph-Powered Machine Learning you will learn: The lifecycle of a machine learning project Graphs in big data platforms Data source modeling using graphs Graph-based natural language processing, recommendations, and fraud detection techniques Graph algorithms Working with Neo4J Graph-Powered Machine Learning teaches to use graph-based algorithms and data organization strategies to develop superior machine learning applications. You'll dive into the role of graphs in machine learning and big data platforms, and take an in-depth look at data source modeling, algorithm design, recommendations, and fraud detection. Explore end-to-end projects that illustrate architectures and help you optimize with best design practices. Author Alessandro Negro's extensive experience shines through in every chapter, as you learn from examples and concrete scenarios based on his work with real clients! about the technology Identifying relationships is the foundation of machine learning. By recognizing and analyzing the connections in your data, graph-centric algorithms like K-nearest neighbor or PageRank radically improve the effectiveness of ML applications. Graph-based machine learning techniques offer a powerful new perspective for machine learning in social networking, fraud detection, natural language processing, and recommendation systems. about the book Graph-Powered Machine Learning teaches you how to exploit the natural relationships in structured and unstructured datasets using graph-oriented machine learning algorithms and tools. In this authoritative book, you'll master the architectures and design practices of graphs, and avoid common pitfalls. Author Alessandro Negro explores examples from real-world applications that connect GraphML concepts to real world tasks. about the audience For readers comfortable with machine learning basics. about the author Alessandro Negro is Chief Scientist at GraphAware. He has been a speaker at many conferences, and holds a PhD in Computer Science. The single best source of information for graph-based machine learning. Odysseas Pentakalos, SYSNET International, Inc I learned a lot. Plenty of 'aha!' moments. Jose San Leandro Armendáriz, OSOCO.es Covers all of the bases and enough real-world examples for you to apply the techniques to your own work. Richard Vaughan, Purple Monkey Collective NARRATED BY JULIE BRIERLEY.